Kontribusi Pendidikan Entrepreneurship: Suatu Upaya Konstruktif Menumbuhkan Jiwa Wirausaha Pada Mahasiswa - Dainuri Dainuri (JOURNAL OF SHARIA ECONOMICS, 2019)
Abstact In a developing country, the role of entrepreneurs cannot be ignored especially in carrying out development. A nation will develop faster if it has entrepreneurs who can create and innovate optimally, which is to realize new ideas into real activities in each of their businesses. Indonesia as a developing country is working hard to improve the lives of its people. One important role in improving the standard of living of its people is through education. Entrepreneurship education is one form of application of the world's care for education to the progress of the nation. In entrepreneurship education it is shown, among others, the value and form of work to achieve success. Entrepreneurship education is a help to teach Indonesian people so that they have a dynamic and creative personal power in accordance with the personality of the Indonesian people based on Pancasila. fostering the spirit of entrepreneurship is one of the important things to be job opportunities, income and welfare for everyone/individual. Keywords: Education, Entrepreneurship Education, Student